Dropping out of school - M. Teneva (Trakia Journal of Sciences)
The modern technological society needs educated people who, through their high professionalism, are called upon to create its progress. In this aspect, a serious problem stands out – the dropout from school of a large number of children, adolescents and young people. The object of the research is the premature interruption of training for a large number of Bulgarian students. The subject of the study is the causes that provoke the students’ dropping out of school. The aim is to differentiate the negative factors leading to dropping out of school, and to identify the motivating factors that encourage the individual to return to the educational environment. In order to realize the so set target, a specially designed test-questionnaire has been used. The survey was conducted among students attending evening courses who have left their education for various reasons and are currently back to the school institution. The contingent of the study includes 120 students from the evening schools. The results indicate that the reasons which prompted the students to leave school early differentiate into four groups: family, social, economic, educational, personal. The motivation to return to school has been dictated in the highest degree by the need for realization of the person on the labor market, followed by the possibility for full social functioning.